2021
DOI: 10.1111/cmi.13311
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis glyceraldehyde‐3‐phosphate dehydrogenase plays a dual role—As an adhesin and as a receptor for plasmin(ogen)

Abstract: The spread of infection is directly determined by the ability of a pathogen to invade and infect host tissues. The process involves adherence due to host–pathogen interactions and traversal into deeper tissues. Mycobacterium tuberculosis (Mtb) primarily infects the lung but is unique in its ability to infect almost any other organ of the human host including immune privileged sites such as the central nervous system (CNS). The extreme invasiveness of this bacterium is not fully understood. In the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Recombinant pneumococcal glycolytic proteins, including GAPDH (Glyceraldehyde 3-phosphate dehydrogenase) and FBA [ 40 ], are produced inside Escherichia coli and elicit the production of antibodies that exhibit specificity towards various serotypes. Research [ 41 ] shows an observed interaction between pneumococcal serotypes and vaccinations targeting choline-binding enzymes (CBPs).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant pneumococcal glycolytic proteins, including GAPDH (Glyceraldehyde 3-phosphate dehydrogenase) and FBA [ 40 ], are produced inside Escherichia coli and elicit the production of antibodies that exhibit specificity towards various serotypes. Research [ 41 ] shows an observed interaction between pneumococcal serotypes and vaccinations targeting choline-binding enzymes (CBPs).…”
Section: Discussionmentioning
confidence: 99%
“…The ECM degradation definitely increases the bacterial invasion into tissue and facilitates invasion and dissemination within the infected host as already has been shown for other pathogens ( Pancholi and Fischetti, 1998 ; Bergmann et al, 2005 ; Lahteenmaki et al, 2005 ; Hemmadi and Biswas, 2021 ). Whereas we proved the binding of SlEno to different ECM proteins using rather indirect methods, Gani et al (2021) applied two different genetic manipulation strategies (overexpression and a siRNA strategy) to show a binding of the glyceraldehyde 3-phosphate dehydrogenase (GAPDH) of Mycobacterium tuberculosis with ECM matrix and the ability to recruit plasmin(ogen) ( Gani et al, 2021 ). Thus, new molecular methods should be evolved to analyze further moonlighting candidates in S. lugdunensis and are currently under intensive investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several additional mycobacterial adhesins have been identified that bind host extracellular matrix proteins [166][167][168][169][170]. To name a few briefly, these include Rv1759c (a PE_PGRS that binds fibronectin) [171], malate synthase (a glyoxalate shunt enzyme that is secreted by an unknown mechanism and that binds laminin as well as fibronectin) [172], and GAPDH (a glycolytic enzyme that binds plasminogen and plasmin with relatively high affinity hence offering a means to degrade extracellular matrix components) [173].…”
Section: Multifunctional Mycobacterial Adhesinsmentioning
confidence: 99%